2019
DOI: 10.1021/acs.inorgchem.9b02782
|View full text |Cite
|
Sign up to set email alerts
|

Highly Photoluminescent Blue Ionic Platinum-Based Emitters

Abstract: New cycloplatinated N-heterocyclic carbene (NHC) compounds with chelate diphosphines (P^P) as ancillary ligands: [Pt(R-C^C*)(P^P)]PF6 (R = H, P^P = dppm 1A, dppe 2A, dppbz 3A; R = CN, P^P = dppm 1B, dppe 2B, dppbz 3B) have been prepared from the corresponding starting material [{Pt(R-C^C*)(µ-Cl)}2] (R = H, A, R = CN, B) and fullycharacterized. The new compound A has been prepared by a stepwise protocol. The photophysical properties of 1A-3A and 1B-3B have been widely studied and supported by the time-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…The X-ray study of 6A , 6B , and 7A (Figures , S56, and S57 and Table ) confirmed their molecular structures showing a really distorted square-planar coordination environment for the metal with C(1)–Pt–C(10) and X(1)–Pt–X(2) (X = P for 6A and 6B , S for 7A ) bite angles of 79°–73°. Regarding the “Pt­(C^C* A/B )” moiety, the Pt–C bond parameters are similar to those of reported platinacycles with N-heterocyclic carbenes, ,,,, and the five-membered platinacycle and the Pt coordination plane result almost coplanar (Table ).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The X-ray study of 6A , 6B , and 7A (Figures , S56, and S57 and Table ) confirmed their molecular structures showing a really distorted square-planar coordination environment for the metal with C(1)–Pt–C(10) and X(1)–Pt–X(2) (X = P for 6A and 6B , S for 7A ) bite angles of 79°–73°. Regarding the “Pt­(C^C* A/B )” moiety, the Pt–C bond parameters are similar to those of reported platinacycles with N-heterocyclic carbenes, ,,,, and the five-membered platinacycle and the Pt coordination plane result almost coplanar (Table ).…”
Section: Resultssupporting
confidence: 81%
“…If we compare the powder QY of 5B (7%) and 6B (57%), with [Pt­(C^C* B )­(P^P)]­PF 6 (P^P = dppm, dppe, dppbz) [QY = 10–40%], having the same cyclometalated carbene (C^C* B ) but different P^P ligand, it can be observed the great influence of the chelating diphosphine. Also, compound 6B proved to be among or even better than the best blue Pt­(II) emitters whether in solid state or doped film. ,, , Nonetheless, the CIE coordinates (0.17, 0.30) slightly deviate from the desired ones for deep blue emitters (0.15, 0.22), see Figure .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To increase the stability of an OLED device, a phosphorescent emitter should be characterised by short radiative decay times, as long‐lived excited states enhance the possibility of side reactions that limit the lifetime of an OLED. Most of the CC * platinum(II) complexes exhibit radiative decay times in the order of 5–30 μs, [2a] but in some cases, extremely fast radiative decay times have been observed [3a,c,4f] . In bimetallic platinum(II) complexes where the Pt−Pt distances are shorter than the sum of the Van der Waals radii of the two platinum(II) atoms, strong metallophilic interactions influence the photophysical properties of these emitters and the excited‐state structure [6] .…”
Section: Figurementioning
confidence: 99%
“…195 Pt NMR spectroscopy is a useful technique to probe the environment around the square-planar Pt­(II) complexes. ,, δ­( 195 Pt) values of platinacycles prepared in the present investigation except for the shift of 20 were measured and are given in Table . 195 Pt NMR spectra of 10 – 15 revealed a doublet of doublets in the range δ­( 195 Pt) −3755 to −3917 ppm ( 1 J Pt–P = 3400–3448 and 1438–1499 Hz) due to coupling with two distinct P nuclei.…”
Section: Resultsmentioning
confidence: 99%